Powerpoint and the development of student’s lateral thinking - Muñoz Sierra, Luz Myrian (Universidad Pedagógica y Tecnológica de Colombia, 2013)
The descriptive use of the slideshow, common in classrooms of the School Victor Manuel Lodoño in Viani, Cundinamarca, gave rise to the concern for inquiring about how this activity would favor the capacity for reflection and creativity of students. With this purpose, a research was conducted, focused on identifying how the use of the PowerPoint program contributes to develop the lateral thinking of student in the seventh grade classroom. Cognitivist theory, research projects on creativity, and qualitative research method, with an ethnographic approach, were taken up again, and guidelines of direct observation and interviews with teachers and students were applied. Finally, it was concluded that PowerPoint favors the development of lateral thinking of students based on the mastery they have of the topics and the program, which allows them to energize the interpretative competence by using drawing tools, expressing flexibility, fluency and originality of new ideas, and different schemes in their works, and proposing solutions to various situations. These advantages were highlighted during the activities for the identification of students’ prior knowledge in collaborative work and tasks, in performing functions assigned individually and in groups, and in the guidance and motivation of teachers.